The Comparison of Food Eating Models of Mothers and Their Daughters - Wadolowska, Lidia; Slowinska, Malgorzata Anna; Pabjan-Adach, Kamila; Przybylowicz, Katarzyna; Niedzwiedzka, Ewa (Pakistan Journal of Nutrition, 2007)
The aim of the work was to compare models of food eating by mothers and their daughters. The study included 97 pairs of mothers (43.3±6.0 years old) and their daughters (16.0±3.1 years old). Food intake was described by food frequency intake method using the calibrated FFQ questionnaire. Products were aggregated into 15 groups using the factor analysis and the tree diagram. Using the clusters analysis separately for mothers and daughters clusters were separated, that corresponded with characteristic eating models. Significant correlation between the amount of food eaten by mothers and daughters was proven for all 15 groups of products (from 0.25 to 0.57; p